2009
DOI: 10.1002/da.20571
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and acute stress and the prediction of major depression in women

Abstract: Background This study explored the relatively neglected role of chronic stress in major depression, examining the independent contributions of co-occurring chronic and acute stress to depression, whether chronic stress predicts acute life events, and whether the two types of stress interact such that greater chronic stress confers greater sensitivity—or resistance—to the depressive effects of acute stressors. Methods From a sample of 816 community women, those who had a major depression onset in the past 9 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
218
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(244 citation statements)
references
References 32 publications
20
218
1
5
Order By: Relevance
“…Stress over an extended period of time is related to mental health problems such as depression. 59,60 Indeed, Hammen and her colleagues 59 have found that chronic and acute stresses were significantly associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Stress over an extended period of time is related to mental health problems such as depression. 59,60 Indeed, Hammen and her colleagues 59 have found that chronic and acute stresses were significantly associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…First, environmental aspects refer to how the environment interacts with the domains of functioning, and this is represented on the Y axis of the matrix. For example, exposure to various environmental stressors has been shown to be associated with depressive symptomatology (Doane et al, 2011;Hammen et al, 2009;Hori et al, 2014) and the influence of environmental stressors could be analyzed in association with a given domain of functioning (e.g. depressive symptoms) using various units of analysis (e.g.…”
Section: The Rdoc Frameworkmentioning
confidence: 99%
“…Stress is a major determinant in the development of depression in the general population (Hammen, Kim, Eberhart, & Brennan, 2009;Lee, Jeong, Kwak, & Park, 2010;Monroe & Reid, 2009). Regarding the population of athletes in elite sports, stress is also discussed in relation to depressive syndromes according to Puffer & McShane (1992).…”
Section: Introductionmentioning
confidence: 99%